Measuring Habitual Arm Use Post-stroke With a Bilateral Time-Constrained Reaching Task - Kim, Sujin; Park, Hyeshin; Han, Cheol E.; Winstein, Carolee J.; Schweighofer, Nicolas (Frontiers in Neurology, 2018)
Background: Spontaneous use of the more-affected arm is a meaningful indicator of stroke recovery. The Bilateral Arm Reaching Test (BART) was previously developed to quantify arm use by measuring arm choice to targets projected over a horizontal hemi-workspace. In order to improve clinical validity, we constrained the available movement time, thereby promoting more spontaneous decision making when selecting between the more-affected and less affected arm during the BART. Methods: Twenty-two individuals with mild to moderate hemiparesis were tested with the time-based BART in three time-constraint conditions: no-time constraint, medium, and fast conditions. Arm use was measured across three sessions with a two-week interval in a spontaneous choice block, in which participants were instructed to use either the more-affected or the less-affected arm to reach targets. We tested the effect of time-constraint condition on the more-affected arm use, external validity of the BART with the Actual Amount of Use Test (AAUT), and test-retest reliability across the three test sessions. Results: The fast condition in the time-based BART showed reduced use of the more-affected arm compared to the no-time constraint condition (P < 0.0001) and the medium condition (P = 0.0006; Tukey post hoc analysis after mixed-effect linear regression). In addition, the fast condition showed strong correlation with the AAUT (r = 0.829, P < 0.001), and excellent test-retest reliability (ICC = 0.960, P < 0.0001). Conclusion: The revised BART with a time-restricted fast condition provides an objective, accurate, and repeatable measure of spontaneous arm use in individuals with chronic stroke hemiparesis.